Similarities and Differences of English and Uzbek Aphorisms - Dildora Baratova (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2025)
This article analyses English and Uzbek aphorisms and shows their similarities and differences. In addition, the linguocultural terms that express the culture contained in English and Uzbek aphorisms are illustrated through examples. The content of aphorisms divided into categories in the two languages and their significance in linguocultural studies are described